2013
DOI: 10.4103/0971-4065.120342
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of GSTM1, GSTT1, and MTHFR polymorphisms to end-stage renal disease of unknown etiology in Mexicans

Abstract: Oxidative stress is increased in chronic kidney disease, owing to an imbalance between the oxidative and antioxidant pathways as well as a state of persistent hyperhomocysteinemia. The enzymes glutathione S-transferases (GSTs) and methylenetetrahydrofolate reductase (MTHFR) are implicated in the regulation of these pathways. This study investigates the association between polymorphisms in the Glutathione S-transferase Mu 1 (GSTM1), glutathione S-transferase theta 1 (GSTT1), and MTHFR genes and end-stage renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 23 publications
(30 reference statements)
1
10
0
Order By: Relevance
“…In our study, we found no significant difference in the frequencies of the GSTT1 and GSTM1 null genotypes among Mexican-Mestizo and Tarahumara individuals from the northwestern region of the country. In addition, we observed a high variability in the frequency of the null genotypes for GSTT1 and GSTM1 among the different geographic regions of the country, ranging from 0.03 to 0.17 for GSTT1 and from 0.22 to 0.48 for GSMT1 ( Pérez-Morales et al , 2008 , 2011 ; Sánchez-Guerra et al , 2012 ; Gutiérrez-Amavizca et al , 2013 ; Sandoval-Carrillo et al , 2014 ; García-González et al. , 2015 ; Jaramillo-Rangel et al , 2015 ).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In our study, we found no significant difference in the frequencies of the GSTT1 and GSTM1 null genotypes among Mexican-Mestizo and Tarahumara individuals from the northwestern region of the country. In addition, we observed a high variability in the frequency of the null genotypes for GSTT1 and GSTM1 among the different geographic regions of the country, ranging from 0.03 to 0.17 for GSTT1 and from 0.22 to 0.48 for GSMT1 ( Pérez-Morales et al , 2008 , 2011 ; Sánchez-Guerra et al , 2012 ; Gutiérrez-Amavizca et al , 2013 ; Sandoval-Carrillo et al , 2014 ; García-González et al. , 2015 ; Jaramillo-Rangel et al , 2015 ).…”
Section: Discussionmentioning
confidence: 88%
“…Although studies about the distribution of GSTM1 and GSTT1 null genotypes in a Mexican-Mestizo population have been performed previously ( Pérez-Morales et al , 2008 ; Pérez-Morales et al , 2011 ; Sánchez-Guerra et al. , 2012 ; Gutiérrez-Amavizca et al , 2013 ; Sandoval-Carrillo et al , 2014 ; García-González et al , 2015 ; Jaramillo-Rangel et al , 2015 ) no reports of the prevalence of these variants in Mexican Amerindian individuals are available. Thus, the aim of this study was to determine and compare the frequencies of GSTM1 and GSTT1 null genotypes in Mexican-mestizo and Amerindian individuals (Tarahumara) from the Northwestern part of the country (State of Chihuahua) with those previously found in other regions of Mexico and around the world.…”
Section: Introductionmentioning
confidence: 99%
“…The GSTM1 gene belongs to a group of enzymes that is responsible for the conjugation of GSH to electrophilic xenobiotics thereby playing a key role in the biotransformation and detoxification of xenobiotics and endogenous substances [14]. It was seen in our study population that GSTM1 gene did not show Ct values in 11 out of 43 CKDu patients (25.6%), six out of 14 CKD patients (42.9%), and eight out of sixteen (50%) of the KHI.…”
Section: Discussionmentioning
confidence: 99%
“…The GSTM1 null mutation is a common polymorphism and has also been associated with the end-stage renal disease of unknown etiology in Mexican patients [14]. The GSTM1 null polymorphism individuals were also found to be more vulnerable to organochlorine pesticides leading to the development of CKDu in a study carried out in an Indian population [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation